2018
DOI: 10.1111/1744-7941.12184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of emotional coping on decision to stay in dysfunctional mentoring relationship

Abstract: The question of why mentees stay with a dysfunctional mentor has puzzled many scholars. In this paper, we argue that fresh graduates in an ongoing mentoring relationship are bombarded with feedback from both good and bad events that happen between them and their mentor, making it difficult for the mentee to know, with certainty, if their relationship with the mentor is objectively positive or negative. To decide whether they should stay with a mentor, we propose that mentees will constantly seek clues from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Accordingly, it leads to favorable outcomes at both the individual and organizational levels. However, despite their potential benefits, mentoring programs are not usually as effective as organizations expect them to be (Eby 2007; Ng, Song and Liu 2019). Research has suggested that, like all interpersonal relationships, mentorship is subject to relational problems such as mismatch, deception, sabotage and overdependence (for a review, see Eby 2007), known as negative mentoring experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it leads to favorable outcomes at both the individual and organizational levels. However, despite their potential benefits, mentoring programs are not usually as effective as organizations expect them to be (Eby 2007; Ng, Song and Liu 2019). Research has suggested that, like all interpersonal relationships, mentorship is subject to relational problems such as mismatch, deception, sabotage and overdependence (for a review, see Eby 2007), known as negative mentoring experiences.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our interest is in the effects of formal mentoring support, defined as an organizational program, in which the organization assigns a more experienced senior mentor (e.g., supervisor) to provide support, guidance, and advice to a less experienced protégé for specific purposes (e.g., orientation, knowledge sharing, career development) over a pre‐determined duration (Chun et al, 2012; Wanberg et al, 2006). Understanding how mentoring influences the attitudes and behavior of newcomer–protégés is important because in addition to having more pronounced effects than other socialization interventions (Chao, 2007), research has shown that mentoring continues to be problematic (Ng et al, 2019). Not only has dysfunctional mentoring been found to have deleterious consequences on protégés stress, depression, and intention to quit (Eby et al, 2010; Kim & Choi, 2011), but it can also adversely impact the mentor (e.g., Hu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how mentoring influences the attitudes and behavior of newcomer-protégés is important because in addition to having more pronounced effects than other socialization interventions (Chao, 2007), research has shown that mentoring continues to be problematic (Ng et al, 2019). Not only has dysfunctional mentoring been found to have deleterious consequences on protégés stress, depression, and intention to quit (Eby et al, 2010;Kim & Choi, 2011), but it can also adversely impact the mentor (e.g., Hu et al, 2022).…”
mentioning
confidence: 99%